Anti-inflammatory and analgesic evaluation of hydroalcoholic extract and fractions from seeds of Piper cubeba L. (Piperaceae) - Perazzo, F. F.; Rodrigues, I. V.; Maistro, Edson Luis [UNESP]; Souza, S. M.; Nanaykkara, N. P. D.; Bastos, J. K.; Carvalho, J. C. T.; Souza, G. H. B. de (Manuscript Technomedia LLP, 2013)
Some of the Piper species have been applied for the treatment of several diseases (anti-oxidant, antimicrobial, anti-inflammatory, and analgesic), considering multiple applications used in traditional medicine of different countries. About these, the present study evaluated some biological activities of Piper cubeba, as writhing test induced by acetic acid, ear edema induced by croton oil and paw edema induced by carrageenan were used by evaluated the analgesic and anti-inflammatory activities of crude hydroalcoholic extract (PCE) and its fractions of different polarities of P. cubeba L. seeds. The lethal dose (LD50) and the effective dose (ED50) were evaluated too. Both the PCE and dichloromethane fraction showed decrease values of edema and abdominal constrictions. The results obtained in this study confirm the low toxicity and analgesic and anti-inflammatory activities of PCE from P. cubeba seeds, justifying its use in folk medicine. Copyright © 2013, Phcog.Net, Published by Reed Elsevier India Pvt. Ltd. All rights reserved.
Keywords: Analgesic; Anti-inflammatory; Piper cubeba; Piperaceae; acetic acid; acetic acid ethyl ester; alcohol; analgesic agent; antiinflammatory agent; carrageenan; croton oil; dexamethasone; dichloromethane; hexane; indometacin; Piper cubeba extract; plant extract; sodium chloride; unclassified drug; analgesic activity; animal experiment; animal model; animal tissue; antiinflammatory activity; controlled study; drug efficacy; ear edema; LD 50; male; mouse; nonhuman; pain; paw edema; plant seed; rat; single drug dose; toxicity testing; writhing test